Establishment of Hairy Root Cultures by Agrobacterium Rhizogenes Mediated Transformation of Isatis Tinctoria L. for the Efficient Production of Flavonoids and Evaluation of Antioxidant Activities - Gai, Qing-Yan; Jiao, Jiao; Luo, Meng; Wei, Zuo-Fu; Zu, Yuan-Gang; Ma, Wei; Fu, Yu-Jie (PloS one, 2015)
In this work, Isatis tinctoria hairy root cultures (ITHRCs) were established as an alternative source for flavonoids (FL) production. I. tinctoria hairy root line V was found to be the most efficient line and was further confirmed by the PCR amplification of rolB, rolC and aux1 genes. Culture parameters of ITHRCs were optimized by Box-Behnken design (BBD), and eight bioactive FL constituents (rutin, neohesperidin, buddleoside, liquiritigenin, quercetin, isorhamnetin, kaempferol and isoliquiritigenin) were quali-quantitatively determined by LC-MS/MS. Under optimal conditions, the total FL accumulation of ITHRCs (24 day-old) achieved was 438.10 μg/g dry weight (DW), which exhibited significant superiority as against that of 2 year-old field grown roots (341.73 μg/g DW). Additionally, in vitro antioxidant assays demonstrated that ITHRCs extracts exhibited better antioxidant activities with lower IC₅₀ values (0.41 and 0.39, mg/mL) as compared to those of field grown roots (0.56 and 0.48, mg/mL). To the best of our knowledge, this is the first report describing FL production and antioxidant activities from ITHRCs.